Investigations on the Recovery of the Electrical Properties of Smart Cut™-Transferred SiC Thin Film Using SiC-on-Insulator Structures - Delcroix, Mathieu; Corbin, Lucie; Caridroit, Simon; Moulin, Alexandre; Rouchier, Séverin; Mony, Karine; Masante, Cédric; Troutot, Nicolas; Rolland, Emmanuel; Gelineau, Guillaume; Widiez, Julie; Papon, Anne-Marie; et al. (Materials science forum, 2024)
SiC-on-Insulator (SiCOI) structures fabricated using the Smart Cut™ technique can be of great interest in order to probe the properties of a silicon carbide (SiC) transferred layer, by electrically insulating it from the receiver substrate. In this study, we report the fabrication of such a SiCOI structure using a SiC receiver, as well as its electrical and TEM characterization after high temperature annealing. We highlight a decrease of the transferred layer electrical resistivity with increasing annealing temperature, due to doping reactivation and electron mobility enhancement. After low temperature annealing (1200°C to 1400°C), deep acceptor levels, possibly located in a damaged region near the substrate’s surface, might be responsible of a non negligible electrical compensation. Beyond 1400°C however, the transferred SiC crystal is healed and electron transport is only subjected to shallow nitrogen ionization.